A large-scale analysis of refractive errors in students attending public primary schools in Mexico - Ramírez-Ortiz, Marco Antonio; Amato-Almanza, Mónica; Romero-Bautista, Iván; Klunder-Klunder, Miguel; Aguirre-Luna, Oswaldo; Kuzhda, Iryna; Resnikoff, Serge; Eckert, Kristen Allison; Lansingh, Van Charles (Scientific reports, 2023)
A cross-sectional, retrospective study was conducted from September 2013 through July 2014 to determine the prevalence of refractive errors among students attending public primary schools in Mexico. Among 3,861,156 students at 14,566 public primary schools in all 32 states of Mexico, teachers identified reduced visual acuity in 1,253,589 (32.5%) using visual acuity measurement. Optometrists confirmed 391,498 [31.2%, mean (SD) age: 8.8 (1.9) years; 204,110 girls (52.9%)] had refractive errors using visual acuity measurement and noncycloplegic static retinoscopy. Among 288,537 (72.4%) of children with previous eyeglasses usage data reported, 241,505 (83.7%) had uncorrected refractive errors. Before prescription eyeglasses were provided, 281,891 students (72%) had logMAR visual acuity ≤ 0.2; eyeglasses corrected vision loss in 85.6% (n = 241,352) of them. Simple myopic astigmatism was the most frequent refractive error (25.7%, n = 100,545). Astigmatism > − 1.00 diopters was present in 54.6% of all students with ametropia. The anisometropia rate based on spherical equivalent difference between right and left eye ≥ 1.50 diopters was 3.9% (n = 15,402). Uncorrected refractive errors are an important issue in primary school students in Mexico. An updated study is needed to analyze the evolving trends over the past decade.